Faktor-faktor yang mempengaruhi sikap remaja Terhadap seks pranikah - Nelva - Rina; Yulia Irvani Dewi; Yesi - Hasneli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
This research describes about factors that influence adolescent attitudes toward premarital sex . methodology on this research was a survey design with cross sectional approach. The sample in this research are 200 students SMA N 1 Cerenti with stratified random sampling technique. Measuring instruments was used a questionnaire. The analysis was used univariate and bivariate analysis by Chi-Square test. The results showed that there is have relationship between knowledge and adolescent attitudes toward premarital sex with p value > 0.05 is 0.024 but there was no relationship between peer and adolescent attitudes toward premarital sex with p value = 1.000, there is no relationship of parents and adolescent attitudes toward premarital sex with p value = 0.880 and no relationship of resources and adolescent attitudes toward premarital sex with a P value = 1.000. The results of this research are expected in the school in order to provide education about reproductive health and sexuality education through formal or extracurricular lessons related to sexuality , and to the parents in order to guide and give knowledge about sex to their children growing up. Keywords: Attitudes, exposure information, parents, peers, knowledge